Toxicity mechanisms of nanoparticles in the male reproductive system. (2nd October 2021) - Habas, Khaled; Demir, Eşref; Guo, Chongye; Brinkworth, Martin H.; Anderson, Diana
Abstract: The field of nanotechnology has allowed for increasing nanoparticle (NP) exposure to the male reproductive system. Certain NPs have been reported to have adverse consequences on male germ and somatic cells. Germ cells are the bridge between generations and are responsible for the transmission of genetic and epigenetic information to future generations. A number of NPs have negative impacts on male germ and somatic cells which could ultimately affect fertility or the ability to produce healthy offspring. These impacts are related to NP composition, modification, concentration, agglomeration, and route of administration. NPs can induce severe toxic effects on the male reproduction system after passing through the blood–testis barrier and ultimately damaging the spermatozoa. Therefore, understanding the impacts of NPs on reproduction is necessary. This review will provide a comprehensive overview on the current state of knowledge derived from the previous in vivo and in vitro research on effects of NPs on the male reproductive system at the genetic, cellular, and molecular levels.